DIGITAL LITERACY LEVEL AMONG ENGLISH PROFESSIONAL TEACHERS - Martriwati, Martriwati; Burhayani, Burhayani; Siswana, Siswana (UICELL, 2023)
Digital literacy is the ability to obtain, understand and use information that comes from various sources in digital form (Gilster, 1997). Along with the rapid development of information and communication technology, as well as the demands of the Indonesian Republic law number 14 of 2005, professional teachers are required to not only be able to utilize digital technology but also assess the validity of information obtained from digital sources. Gilster states that there are 4 aspects of competence so that someone is said to be digitally literate, the four aspects are aspects of internet searches, aspects of hypertext direction, aspects of evaluating information content, and aspects of knowledge preparation. This paper aims to analyze the level of digital literacy ability of professional teachers. The study used a quantitative method through Likert- scale questionnaires. The population in this study were all English professional teachers who graduated from a private university. The study found that research participants showed high levels of digital literacy and preparedness to use digital technology. Thus, by integrating digital technology, those professional teachers might meet the digital literacy standards of professional English instructors while also improving the quality of English teaching and learning output. Keywords: Critical-Creative Thinking, Questioning. Young Learners